2005
DOI: 10.1097/01.ta.0000162731.53812.58
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prehospital Endotracheal Intubation on Outcome in Moderate to Severe Traumatic Brain Injury

Abstract: Prehospital intubation is associated with a decrease in survival among patients with moderate-to-severe TBI. More critically injured patients may benefit from prehospital intubation but may be difficult to identify prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
2
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(122 citation statements)
references
References 43 publications
3
108
2
7
Order By: Relevance
“…[5][6][7][8][9] EADs are the most common alternative to intubation in the field and likely the most common rescue airway device for failed intubation, other than bag-mask ventilation. The placement of an EAD can occur quickly, provides a means to oxygenate and ventilate a patient, and in many systems falls within the scope of practice for If the EAD does decrease cerebral perfusion-particularly in patients in a low-flow state-then many of these benefits of EAD placement may be outweighed by increased morbidity and mortality, although this has not been definitively demonstrated by research to date.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] EADs are the most common alternative to intubation in the field and likely the most common rescue airway device for failed intubation, other than bag-mask ventilation. The placement of an EAD can occur quickly, provides a means to oxygenate and ventilate a patient, and in many systems falls within the scope of practice for If the EAD does decrease cerebral perfusion-particularly in patients in a low-flow state-then many of these benefits of EAD placement may be outweighed by increased morbidity and mortality, although this has not been definitively demonstrated by research to date.…”
Section: Discussionmentioning
confidence: 99%
“…One study adjusted for GCS, 40 another 29 did not. Adjustment for GCS was unclear in one study 28 and was not reported for the TBI subgroup in another. 7 In 10 studies with groupspecific information on the severity of TBI, the mean or median AIS of head region ranged from 3.2 7 to 5.1 29 in the intubation groups, and from 2.7 7 to 5.0 31 in the control groups.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In three of these studies, 7 28 29 the difference between the groups was 5 ISS points or more. Adjustment for ISS was not done in one study, 29 unclear in another, 28 and not reported for the subgroup of headinjured patients in yet another study. 7 Pre-hospital intubation and mechanical ventilation In four articles, 32 35 36 40 pre-hospital intubation and ventilation protocols were described in detail.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations